Study of mass and cluster flux in a pulsed gas system with enhanced nanoparticle aggregation; Journal of Applied Physics; Vol. 116, iss. 14 - Drache S. Steffen; Stranak V. Vitezslav; Hubicka Z. Zdenek; Berg F. Florian; Tichy M. Milan; Helm Ch. A. Christiane; Hippler R. Rainer (2014, 2014)
Title screen